2020
DOI: 10.1038/s41467-019-13872-1
|View full text |Cite
|
Sign up to set email alerts
|

An early phase of instructive plasticity before the typical onset of sensory experience

Abstract: While early experience with moving stimuli is necessary for the development of direction selectivity in visual cortex of carnivores, it is unclear whether experience exerts a permissive or instructive influence. To test if the specific parameters of the experienced stimuli could instructively sculpt the emergent responses, visually naive ferrets were exposed to several hours of experience with unusual spatiotemporal patterns. In the most immature ferrets, cortical neurons developed selectivity to these pattern… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 51 publications
1
32
0
1
Order By: Relevance
“…Immune checkpoint inhibitors block these inhibitory receptor-ligand interactions restoring anti-cancer immunity [ 82 ]. Several immune checkpoints and checkpoint inhibitors exist, but the most studied and prescribed immune checkpoint inhibitors target PD-1/PD-L1 [ 83 ]. Canonically, PD-1 is expressed by T cells and PD-L1 is expressed by tumor cells.…”
Section: Microfluidic Chipsmentioning
confidence: 99%
“…Immune checkpoint inhibitors block these inhibitory receptor-ligand interactions restoring anti-cancer immunity [ 82 ]. Several immune checkpoints and checkpoint inhibitors exist, but the most studied and prescribed immune checkpoint inhibitors target PD-1/PD-L1 [ 83 ]. Canonically, PD-1 is expressed by T cells and PD-L1 is expressed by tumor cells.…”
Section: Microfluidic Chipsmentioning
confidence: 99%
“…A recently published report showed a case with significant interstitial lymphocyte infiltrates in the lung tissue, lymphopenia, and hyperactivation of T-cells in peripheral blood [ 6 , 7 ]. Inflammatory and immune responses are important to eliminate infection, but may have a significant impact on SARS-CoV-2 pathogenesis, and may play a role in the expression of the clinical spectrum of COVID-19 disease [ 9 ]. Following SARS-CoV-2 infections, abnormal release of cytokines and pro-inflammatory molecules are closely related to lung injury [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation for the synchronous refinement of interareal circuits in the ferret visual cortex could be the delayed eye opening in this altricial species which is around P30 (Linden et al, 1981;Walsh and Guillery, 1985). This may cause the maturation of these cortical circuits in ferrets to be largely dependent on intrinsic activity, whereas plasticity dependent mechanisms driven by visual activity emerge shortly afterward (Ruthazer and Stryker, 1996;Sengpiel and Kind, 2002;Roy et al, 2018Roy et al, , 2020. Furthermore, this pattern of refinement may also be functionally crucial for the concurrent establishment of RF properties in multiple cortical areas mediated via feedforward projections, and the integration of inputs carried out by feedback circuits.…”
Section: Patterns Of Visual Cortical Development (Hierarchical Versusmentioning
confidence: 99%
“…Developmental events in the early phase of life depend on spontaneous neuronal activity before the period of eye opening and in certain instances rely on light passing through unopened eyelids (Krug et al, 2001;Colonnese et al, 2010;Xu et al, 2011;Ackman et al, 2012). A recent innovative study in ferrets demonstrated that visual development progresses through neural activity occurring before and at eye opening (Roy et al, 2020). Visual stimulation through closed and opening eyelids serves in shaping the neuronal response properties and provides instructive signals for cortical circuit formation (Roy et al, 2020).…”
Section: Role Of Visual Experience and Effect Of Deprivation During Tmentioning
confidence: 99%
See 1 more Smart Citation